Liver Mesenchymal Hamartoma - Nuria Cahís Vela; Inés Loverdos Eseverri; Viviana Patricia Beltrán Salazar; Nuria Brun Lozano; Joan Carles Ferreres Piñas; Carlos José Ruiz Hernández (Elsevier, 2021)
Liver Mesenchymal Hamartoma (LMH) is a rare benign lesion occurring primarily in the pediatric population. The pathogenesis is not certain, although an association has been seen with abnormal mesodermal synchronous development in the portal tract. A 4-year-old female patient, with no relevant personal and family history, was evaluated for abdominal distension. Hepatomegaly was detected as a casual finding. Image tests showed a multiseptae cystic lesion in the right lobe of the liver. Gross pathological review of the lesion identified a cystic consistency tumor occupying the entire right lobe and displacing suprahepatic vessels, gallbladder and vascular pedicle. Complete dissection was performed. Histologically studies showed a smooth and shiny external surface, multiloculated, with a liquid content exit of yellowish coloration and thickened walls with areas of yellowish coloration and focally of increased consistency. The mass consisted on cystic neoplasm of thickened walls and abundant vessels, with calcified areas, as well as dilated biliary and lymphatic ducts and mild associated chronic inflammatory component. The patient was discharged home on postoperative day seven. A review of the literature for LMH in children reports a few publications, most of them limited to case reports. LMH has the potential for mixed pathology, multifocality, incomplete regression and rare malignant transformation, so it is important to make a correct differential diagnosis in order to not underdiagnose.